The Effectiveness Of K-W-L Technique To Increase Students’ Reading Comprehension Achievement Through Reading Descriptive Text For Grade 8 of SMP Negeri 1 Cisarua - Situmorang, Nelson Balisar Panjaitan, Radema (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2018)
The purpose of this study is to find out whether there is a significant difference in reading comprehension achievement between those who are taught using the K-W-L (Know-Want to know-Learn) technique and those who are taught using the Conventional technique. In this study, the researcher used quantitative research. The participants of this study were students at SMP Negeri 1 Cisarua, Bandung. This study was conducted in ten meetings. This research was conducted in four steps: Pilot test, Pre-test, treatment (K-W-L technique) and post-test. After analyzing the data from the result of pre-test and post-test score it showed that there is significant difference in reading comprehension between those who are taught using K-W-L technique and those who are taught using conventional technique. Therefore, it can be concluded that the K-W-L technique as a teaching material has a positive impact in reading comprehension achievement.Key Word: K-W-L technique, Effectiveness, and Reading Comprehension.